Building University Schools in Teacher Education Programmes Guidelines and Suggestions - Lazarová, Bohumíra (Masaryk University Press, 2021)
Pre-gradual teacher education involves students' practice teaching as carried out in so-called university schools or faculty schools. The objective of this digital handbook is to provide various options of implementation of university school concepts in teacher education programmes. General ideas and specific steps comprising organization of collaboration-supporting practices, internship activities and requirements for school-based teacher educators' competences are presented within this structure. This digital handbook is one of the outputs of Enhancing European Teacher Education through University Schools, an Erasmus+ EdUSchool project aimed to develop a common European understanding of university schools and their concepts among all stakeholders.